Improvement of reading comprehension and rhetoric speaking skills of elementary school students through mind-mapping strategies - Ari Kusmiatun (LPPM UNY, 2008)
Abstract: This action research study aimed at improving students skills in reading comprehension and rhetoric speaking through mind-mapping strategies. The study was conducted at SD Muhammadiyah Purwodiningratan2 Yogyakarta. The subjects were 29 students in the VIa class consisting of 17 boys and 12 girls. Data were gathered by the use of intensive observations,questionnaires, and interviews. The study was conducted in two cycles. The results showed that the application of mind-mapping strategies in Bahasa Indonesia teaching-learning process, could improve students' speaking and reading skills